PERHITUNGAN HARGA POKOK PRODUKSI : SEBUAH ANALISIS PERBANDINGAN ANTARA METODE FULL COSTING DENGAN ACTIVITY BASED COSTING SYSTEM PADA PT. "Y" - Muhadi Muhadi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2010)
In general, every company wants to exist in its business although there are many competiiors to attract both home markets and overseas markets. To face the competition, the company needs to have the right action in implementing its managerial functions, i.e. by changing the production process through automatization enhancement in order to press its selling price. As a result, the company will be able to compete and to attract more markets. A good efficiency, productivity and effectivity of production process will make a low selling price and a quality product. It can be implemented if there is a management or costing system which can arrange that process. One of the concepts supporting the new cost management is Activity Based Costing System as a supplement of the old cost accounting system. The research method used is a descriptive research method. The descriptive research method is a research which aims at making a description of material systematically, factually, and accurately concerning facts and characteristics of the research population to know the comparison between Full Costing Methodology and Activity Based Costing System. Obviously, there is a difference in cost production that influences the determination of selling price. Thus, the determination of selling price resulting in profits acquired is also different.